Role of the Psychiatric Nurse in Improving the Psychosocial Health of Families After Suicide - Zahide Gül Yazgı; Mualla Yılmaz (Psikiyatride Güncel Yaklaşımlar, 2023)
Suicide is defined as death that occurs as a result of deliberate self-harming behavior with the intention of ending one's life. Each suicide has many physical, economic and psychological short and long-term effects on the individual, family, friends and society. The death of an individual as a result of suicide creates a traumatic effect for family members and causes family members to experience various psychosocial problems. For this reason, it is very important to focus on the consequences of suicide in family members who have lost due to suicide, to evaluate the family's reactions to suicide, and to provide the needed psychosocial support. In this context, in this review, it is aimed to review the literature on the psychosocial problems experienced by families who have lost due to suicide and to present up-to-date information on the role of psychiatric nurse in improving the psychosocial health status of families.